The Future of Data: Too Much Visualization Too Little Understanding? - Reitsma,Reindert; Marks,Andrea (Dialectic, 2019)
Data is part of our lives. Information visualizations help us make sense of this data and possibly help us make changes because of it. In this paper, however, we estimate some of the consequences of what seems an ominous trend, namely the needless complication and beautification of such visualizations. We argue that with increased availability of data and ever more powerful and easy to use visualization software, it becomes easy to succumb to the temptation to impress rather than to communicate. And so we wonder: is a future filled with visualizations that are visually complex and stunning, yet fail to properly communicate the data emerging? To assess some of the consequences of this practice we selected five examples from published sources, developed far simpler (and less attractive) versions from the identical data, randomly exposed these visualizations to subjects and asked simple questions about the displayed data. We find that, on average, it takes subjects longer to comprehend the complex versions, that it takes subjects longer to extract information from these versions and that they make more and larger errors doing so. The experiment shows that subjects eventually do learn how to navigate the complex versions, but by then they have spent significantly more time and made serious interpretative errors.
Keywords: BIS; Design Program